Serverless architectures with Kubernetes : create production-ready Kubernetes clusters and run serverless applications on them /: create production-ready Kubernetes clusters and run serverless applications on them. (2019) - Yilmaz, Onur; Sarathchandra, Sathsara
No abstract available